Nigeria in the COVID era: Health system strengthening for national security and prosperity - Odusanya, Olumuyiwa (The Nigerian postgraduate medical journal, 2022)
The coronavirus disease-19 pandemic has spread to all parts of the world. As of 20 May 2022, over 500 million confirmed cases have occurred with over 6 million deaths. In Nigeria, over 255,000 cases have occurred with more than 3000 deaths. The pandemic has adversely affected virtually all aspects of human endeavour, with a severe impact on the health system. The Nigerian health system was ill prepared for the pandemic, and this further weakened it. The impacts of the pandemic on the health system include disruption of health services, low motivation of the health workforce, unresponsive leadership and poor funding. The national response, though initially weak, was ramped up to expand capacity building, testing, public enlightenment, creation of isolation and treatment centres and research. The funding for the national response was from the government, private sector and multilateral donors. Nigeria must comprehensively strengthen its health system through motivating and building the capacity of its human resources for health, improved service delivery and provision of adequate funding, to be better prepared against future pandemics.